Peningkatan Pengetahuan Masyarakat Mengenai Penggunaan Obat Kortikosteroid - Vidya Kartikaningrum; Diah Nurcahyani; Andita Nur Wijayanti; Erlien Dwi Cahyani; Christianto Adhy Nugroho (jurnal ABDIMAS Indonesia, 2025)
Corticosteroids are hormones that play an important role in the human physiological system, affecting self-defense against environmental changes. However, the perception of their efficacy often drives irrational self-medication behavior in the community, which can lead to detrimental effects if used long-term without supervision. This community service activity was carried out in Kepolorejo Village, Magetan Regency, based on initial observations showing errors in corticosteroid use, such as doubling dosages. The method used was educational counseling with material presentation and Q&A discussions regarding irrational corticosteroid use. Knowledge measurement was conducted through pre-test and post-test questionnaires. The results showed an increase in public knowledge regarding the impact of irrational steroid use.